2003
DOI: 10.1046/j.1365-2419.2003.00253.x
|View full text |Cite
|
Sign up to set email alerts
|

Abundance of Calanus sinicus across the tidal front in the Yellow Sea, China

Abstract: The abundance of Calanus sinicus eggs, nauplii, copepodites and adults and chlorophyll a (Chl‐a) concentration were studied across tidal fronts in October 2000, and May and June 2001 in the Yellow Sea, China. The aim of the study was to evaluate the role of tidal fronts in the ecology of C. sinicus. The hydrographic tidal fronts were identified by the horizontal temperature gradient in the bottom layer and the temperature profiles across the fronts. The survey results showed that the concentration of Chl‐a was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 19 publications
2
19
1
Order By: Relevance
“…The strong convection currents between coastal and offshore waters formed in some seasons can enhance the coastal nutrient transporting to offshore waters (Yuan and Hsueh, 2010;Yuan et al, 2008). Liu et al (2003) observed high primary and secondary production at Yellow Sea fronts and Huang et al (2010) found a good match between the position of major spawning grounds and the position of coastal fronts. The variability of Chla between coastal and offshore waters may be responding to the variations in frontal structures on seasonal and inter-annual time scales.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…The strong convection currents between coastal and offshore waters formed in some seasons can enhance the coastal nutrient transporting to offshore waters (Yuan and Hsueh, 2010;Yuan et al, 2008). Liu et al (2003) observed high primary and secondary production at Yellow Sea fronts and Huang et al (2010) found a good match between the position of major spawning grounds and the position of coastal fronts. The variability of Chla between coastal and offshore waters may be responding to the variations in frontal structures on seasonal and inter-annual time scales.…”
Section: Introductionmentioning
confidence: 85%
“…They follow the 50 m isobath and play key roles in nutrient transport and high productivity (Hickox et al, 2000;Huang et al, 2010;Liu et al, 2003). The strong convection currents between coastal and offshore waters formed in some seasons can enhance the coastal nutrient transporting to offshore waters (Yuan and Hsueh, 2010;Yuan et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of how aggregations of N. nomurai respond to the tidal front in the YS was undetermined. Their increased abundance could reflect the locally high chlorophyll a concentration and zooplankton biomass (Liu et al, 2003), or the interaction between frontal circulation and their swimming behavior (Purcell et al, 2000).…”
Section: Large-scale Distributions Of Jellyfish In Chinese Watersmentioning
confidence: 99%
“…and Paracalanus spp., followed by Acartia spp., Labidocera spp., Corycaeus spp., and immature copepods. C. sinicus is one of the key copepod species in the Yellow Sea (Jang and Kim, 1998) and East China Sea ecosystems and comprises about 85% of the total zooplankton biomass in the Yellow Sea in the spring (Liu et al, 2003). Compared to small copepods such as P. indicus and A. omorii, C. sinicus was susceptible to active predation by anchovy and sardine (Uye et al, 1990).…”
mentioning
confidence: 99%